The novel HALO mini-DOAS instrument: inferring trace gas concentrations from air-borne UV/visible limb spectroscopy under all skies using the scaling method - Hüneke, Tilman; Aderhold, Oliver-Alex; Bounin, Jannik; Dorf, Marcel; Gentry, Eric; Großmann, Katja; Heckl, Mareike; Knapp, Marvin; Knecht, Matthias; Lörks, Dominique; Ludmann, Sabrina; Raecke, Rasmus; et al. (Atmospheric measurement techniques discussions, 2017)
We report on a novel 6 channel optical spectrometer (further on called mini-DOAS instrument) for aircraftborne nadir and limb measurements of atmospheric trace gases, liquid and solid water, and spectral radiances in the UV/vis and nearIR spectral ranges. The spectrometer was developed for measurements from aboard the HALO (http://www.halo.dlr.de/) research aircraft during dedicated research missions. Here we report on the relevant instrumental details and the novel scaling method used to infer the mixing ratios of UV/vis absorbing trace gases from their absorption measured in limb geometry. The uncertainties of the scaling method are assessed for NO2 and BrO measurements. Some first results are reported along with complementary measurements and comparisons with model predictions for a selected HALO research flight from Cape Town to Antarctica, which was performed during the research mission ESMVal on 13 September 2012.